KAJIAN EKSPRESIF TERHADAP NOVEL KEMARAU KARYA A.A. NAVIS - Galang Garda Sanubari; Titik Maslikatin; Heru S.P. Saputra (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
The Drought Novel by A.A. Navis is the object of this research. Tells the life of a middle-aged man who lives in a village. His desire to change the way people around him think about work and make sense of life is hampered by their nature and personal past. Explicitly this novel is like discussing the life of the main character. The reality behind it, culture, innuendo, and religious observance neatly packaged in it. Therefore from that novel that is able to load content in the form of reality and expression of the author, the researcher chooses Dynamic Structuralism as the study theory. Will be achieved in this article the approach used only from the perspective of the expressive approach. The method used is reading, recording, watching, recording data on film sources, and processing data. The results of this study resulted in the study of extrasic (expressive) Sasra works, criticism of the authors of the work on human behavior, the introduction of several Minangkabau cultures, and personal experiences of A.A. Navis